What Do Remittances Do? : Analyzing the Private Remittance Transmission Mechanism in El Salvador - Caceres, Luis Rene (IMF Working Papers; Working Paper ;, 2006)
Family remittances are important for El Salvador's economy. This paper analyzes the impact of remittances on El Salvador's economy and the spillover effects on the other Central American countries. A vector autoregression (VAR) model is formulated, consisting of real and monetary variables. The results suggest that in, El Salvador, remittances lead to decreases in economic activity, international reserves, and money supply and increases in the interest rate, imports, and consumer prices. This underscores the need for reorienting economic policy in El Salvador to promote the use of remittances in capital formation activities to maximize the benefit of remittances.